The Impact of Women Empowerment on Poverty Reduction in Rural Area of Bangladesh: Focusing on Village Development Program - Showkot Jahan Nadim; Adie Dwiyanto Nurlukman (Universitas Muhammadiyah Tangerang, 2017)
Women empowerment is one of the most discussing issues in the present world, especially in the developing country. Bangladesh is one of the developing countries with almost 50% women of it’s total population. In labor force women participation is arround 57.30%, and facing many kinds of obstacles like they have family burden, social burden, religion burden mostly in rural area. Empowerment can be defined by giving power and authority to take decision in every part of life, including household, economic, social, political etc. Women empowerment can be considered as a weapon for alleviating poverty. Since achieving independence, poverty has been dominating in Bangladesh. For alleviating poverty, it is important to take apart by government and non-government organizations. In this regarding that women can play a vital role with those organization. The purpose of the research, to analyze the real effect of women empowerment on poverty reduction and make recommendation for developing the situation. Pemberdayaan perempuan adalah salah satu masalah yang paling banyak dibahas di dunia saat ini, terutama di negara berkembang. Bangladesh adalah salah satu negara berkembang dengan populasi wanita hamper sekitar 50%. Berdasarkan angkatan kerja, partisipasi perempuan sekitar 57,30%, serta menghadapi berbagai macam hambatan seperti memiliki beban keluarga, beban sosial, beban agama dan sebagian besarnya hidup di daerah pedesaan. Pemberdayaan dapat didefinisikan dengan memberikan kekuasaan dan otoritas untuk mengambil keputusan di setiap bagian kehidupan, termasuk rumah tangga, ekonomi, sosial, politik dll. Pemberdayaan perempuan dapat dianggap sebagai senjata untuk mengurangi kemiskinan. Sejak kemerdekaan, kemiskinan telah mendominasi di Bangladesh. Untuk mengurangi kemiskinan, penting untuk dibongkar oleh organisasi pemerintah dan non-pemerintah. Dalam hal ini perempuan dapat memainkan peran penting dengan organisasi tersebut. Tujuan dari penelitian ini, untuk menganalisis pengaruh nyata pemberdayaan perempuan terhadap pengurangan kemiskinan dan membuat rekomendasi untuk mengembangkan situasi.